2010
DOI: 10.1042/bj20101338
|View full text |Cite
|
Sign up to set email alerts
|

Human OGA binds substrates in a conserved peptide recognition groove

Abstract: Modification of cellular proteins with O-GlcNAc (O-linked N-acetylglucosamine) competes with protein phosphorylation and regulates a plethora of cellular processes. O-GlcNAcylation is orchestrated by two opposing enzymes, O-GlcNAc transferase and OGA (O-GlcNAcase or β-N-acetylglucosaminidase), which recognize their target proteins via as yet unidentified mechanisms. In the present study, we uncovered the first insights into the mechanism of substrate recognition by human OGA. The structure of a novel bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 32 publications
(39 reference statements)
1
63
0
Order By: Relevance
“…PNP-GlcNAc is an artificial chromophoric substrate for bGlcNAcase, such as the O-GlcNAcases in metazoans [26]; and the glucosaminidases and chitobiases in bacteria [6,22]. In this work we showed that the inactivation of NagZ xc decreased about 40% of the activity for pNP-GlcNAc.…”
Section: Discussionmentioning
confidence: 64%
“…PNP-GlcNAc is an artificial chromophoric substrate for bGlcNAcase, such as the O-GlcNAcases in metazoans [26]; and the glucosaminidases and chitobiases in bacteria [6,22]. In this work we showed that the inactivation of NagZ xc decreased about 40% of the activity for pNP-GlcNAc.…”
Section: Discussionmentioning
confidence: 64%
“…Bacterial homologues have previously been used to gain insights into the structure, mechanism and substrate recognition of the metazoan OGA-GH84 catalytic domain [30,32,34]. Of particular interest is a GH84 from the marine bacterium Oceanicola granulosus , Og OGA, which was recently crystallized [34], as it shows higher sequence identity to hOGA when compared with other bacterial OGA homologues, with sequence conservation extending beyond the catalytic core revealing a conserved peptide-binding groove [34]. Strikingly, close inspection of the Og OGA genomic location reveals an open reading frame coding for a predicted AT [25,38] immediately downstream of the Og OGA gene (figure 1 a ).…”
Section: Resultsmentioning
confidence: 99%
“…For OGA, our knowledge of how this enzyme recognizes substrates is still less understood. Structures of bacterial homologues of hOGA have been determined (32,46,47), and a conserved peptide substrate binding groove has been proposed (47); however, no detailed kinetic studies evaluating hOGA activity on O-GlcNAc-modified proteins have been performed. To gain insight into the processing of protein substrates by these two enzymes, we performed a series of kinetic studies examining both hOGT and hOGA activity on five structurally diverse proteins that can be recombinantly expressed at high levels within E. coli both in an O-GlcNAc-modified form and in their unmodified state.…”
Section: Discussionmentioning
confidence: 99%